The ecological handicap of the tropics - Peter P. Waller (Intereconomics, 1984)
The long-forgotten subject of the ecological disadvantages of the tropics has been brought to the fore once again by the catastrophic droughts in the Sahel and in southern Africa. The naive belief that economic development is simply a matter of finding the right technology and of spreading scientific knowledge must give way to the acknowledgement that the “development threshold” of the tropical countries is very substantial and complex, and that surpassing it will be a long and wearisome business.
Keywords: 330; Tropical Regions